2011
DOI: 10.1017/s1461145711000861
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of munc18-1 and syntaxin-1A interactive partners in schizophrenia prefrontal cortex: down-regulation of munc18-1a isoform and 75 kDa SNARE complex after antipsychotic treatment

Abstract: Munc18-1 and syntaxin-1 are crucial interacting molecules for synaptic membrane fusion and neurotransmitter release. Contrasting abnormalities of several proteins of the exocytotic machinery, including the formation of SNARE (synaptobrevin, SNAP-25 and syntaxin-1) complexes, have been reported in schizophrenia. This study quantified in the dorsolateral prefrontal cortex (PFC, Brodmann area 9) the immunocontent of munc18-1a/b isoforms, syntaxin-1A, other presynaptic proteins (synaptotagmin, synaptophysin), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 69 publications
4
40
1
Order By: Relevance
“…The study design was approved by the Ethical Committee of Clinical Investigation (CEIC, Spain) and developed in accordance with the guidelines of the University of the Balearic Islands. Caucasian subjects who had died of various causes were subjected to a retrospective search for previous psychiatric diagnoses (DSM-IV) and medications as described (Gil-Pisa et al 2012 ;Urigü en et al 2009). Healthy controls (no evidence of psychiatric or neurological disorder) and subjects with SZ or MD were included in the study.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The study design was approved by the Ethical Committee of Clinical Investigation (CEIC, Spain) and developed in accordance with the guidelines of the University of the Balearic Islands. Caucasian subjects who had died of various causes were subjected to a retrospective search for previous psychiatric diagnoses (DSM-IV) and medications as described (Gil-Pisa et al 2012 ;Urigü en et al 2009). Healthy controls (no evidence of psychiatric or neurological disorder) and subjects with SZ or MD were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Healthy controls (no evidence of psychiatric or neurological disorder) and subjects with SZ or MD were included in the study. These SZ and MD subjects had been used in a previous study that revealed alterations of key proteins of the exocytotic machinery in PFC (Brodmann's area 9 ; BA9) of SZ subjects (Gil-Pisa et al 2012). Subjects with SZ or MD [psychotropic-free : SZ(x) or MD(x); psychotropic-treated : SZ(+) or MD(+)] were matched to control subjects for post-mortem interval (PMI), brain pH, gender and age at death (Table 1 ; see Gil-Pisa et al 2012 for individual features including causes of death and blood/urine levels of psychotropic drugs, which are also reported in the present study as Supplementary Tables S1 and S2).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations